Penerapan Animasi 2d Tentang Kebiasaan Menunda Tugas Di Kalangan Mahasiswa - Jasmine Fitria Dewi; Andreana Lingga Sekarasri (VisArt: Jurnal Seni Rupa dan Design, 2025)
The habit of delaying assignments, or procrastination, is a common behavior frequently found among university students, and it can negatively affect both their academic performance and psychological well-being. Factors such as poor time management, fear of failure, and low motivation are the main causes of this behavior. This study aims to design a 2D animation as an educational medium that visually and engagingly illustrates the negative impacts of procrastination. The methods employed include observation, interviews, and literature review, with a focus on developing the concept and character design of the animation. The 2D animation is created without dialogue. In a surrealist style, the world around the main character undergoes distortion, with people transforming into clock-headed figures, symbolizing growing anxiety and fear. The storytelling of this animation is reflected through the journey of the main character, who becomes increasingly trapped in a cycle of procrastination, as the environment and surrounding characters transform in line with the emotions and pressures he experiences. It is expected that this animation can raise students’ awareness of the consequences of procrastination and encourage them to improve their time management